2016
DOI: 10.1053/j.gastro.2016.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Sofosbuvir, Velpatasvir, and GS-9857 in Patients With Genotype 1 Hepatitis C Virus Infection in an Open-Label, Phase 2 Trial

Abstract: In a phase 2 open-label trial, we found 8 weeks of treatment with sofosbuvir-velpatasvir plus GS-9857 to be safe and effective in treatment-naive patients; 12 weeks was safe and effective in patients previously treated with DAAs. The combination was safe and effective in patients with or without compensated cirrhosis. Clinicaltrials.gov no: NCT02378935.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 15 publications
1
50
0
Order By: Relevance
“…Shortening treatment duration also has the potential to improve treatment uptake, adherence, and tolerability, and thereby improve patient outcomes . Although the new pangenotypic combinations of sofosbuvir/velpatasvir and glecaprevir/pibrentasvir have reduced treatment duration to 8 weeks in some patient populations, attempts to shorten treatment duration to fewer than 8 weeks have generally resulted in high viral relapse rates …”
mentioning
confidence: 99%
“…Shortening treatment duration also has the potential to improve treatment uptake, adherence, and tolerability, and thereby improve patient outcomes . Although the new pangenotypic combinations of sofosbuvir/velpatasvir and glecaprevir/pibrentasvir have reduced treatment duration to 8 weeks in some patient populations, attempts to shorten treatment duration to fewer than 8 weeks have generally resulted in high viral relapse rates …”
mentioning
confidence: 99%
“…The most common AEs observed were headache, diarrhea, nausea, and fatigue. Among all the study subjects, only one patient from Group 4 discontinued the treatment due to increased ALT levels (grade 3) [26]. This study suggested the utility of SOF/VOX/VEL in individuals who had failed other therapies [30,26].…”
Section: Clinical Efficacymentioning
confidence: 98%
“…A total of 120 patients were enrolled in this study to evaluate the safety, PK, and antiviral activity of once-daily administration of VEL at doses ranging from 5 to 150 mg for 3 days in patients with genotypes 1–4 HCV infection [25,26]. …”
Section: Clinical Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, pan-genotypic DAA therapies such as velpatasvir, which has recently demonstrated an SVR12 rate approaching 100% when administered for 12 weeks in combination with sofosbuvir [19], have the potential to eliminate the need for genotyping and thereby greatly simplify treatment. GS-9857 [20, 21] and ravidasvir [22] also show significant promise in this area; the latter has demonstrated a 97% SVR12 rate in 182 non-cirrhotic patients with HCV GT4 in Egypt when given for 12 weeks in combination with sofosbuvir [23]. …”
Section: Introductionmentioning
confidence: 99%